Matošev Prologdrami ProkletstvoMilana Ogrizovića i Andrije Milčinovića - Trojan, Ivan (Wydawnictwo Nauka i Innowacje, 2014)
On 7th May 1907, after publishing the play Prokletstvoin literary magazine „Savremenik”, the censorship approved performing the play in the Croatian national theatre in the theater season 1906/1907 under the condition that it would have passed through some radical changes. However, twenty days later all rehearsals were banned. Authors, Milan Ogrizović and Andrija Milčinović, show their brief union in resisting censorship publishing Prokletstvointo a separate book in year 1907 with Matosʼ Prologuethat critically assails the institutions that stopped the play. Content and repercussions of Matosʼ editorial in Prokletstvoare the starting point of this article that outlines the cultural and political situation in Croatia in the fi rst decade of the 20 th century.
Matošʼs Prolog to the Milan Ogrizović’s and Andrija Milčinović’s Play Prokletstvo
Keywords: Milan Ogrizović; Andrija Milčinović Prokletstvo; Antun Gustav Matoš Prologue; individuality; conscience; Croatian Writers Association; theatrical affair; controversy; Censorship